Relationships between weight bias internalization and biopsychosocial health outcomes: A prospective study in Chinese adolescents. Issue 5 (27th January 2023) - Barnhart, Wesley R.; Cui, Shuqi; Cui, Tianxiang; He, Jinbo
Abstract: Objective: An extensive literature has documented the deleterious effects of weight bias internalization (WBI) on biopsychosocial health outcomes. Still, this research is largely confined to the Western context. Furthermore, few studies have explored associations between WBI and biopsychosocial health outcomes, including in non‐Western adolescent populations. Method: The present study explored the longitudinal relationships between WBI and body dissatisfaction, disordered eating, psychosocial impairment related to eating disorder features, and psychological and physical well‐being in a sample ( N = 1549; aged 11–18 years at baseline) of Chinese adolescents. Relationships between study variables were examined between two waves of data measurement (Time 1, baseline, and Time 2, 6‐month). Cross‐lagged and multivariate models were used to explore prospective relationships between WBI and biopsychosocial correlates. Results: Bidirectional relationships were observed between WBI and biopsychosocial correlates in Chinese adolescents. Adjusting for covariates and other predictor variables, higher body dissatisfaction, disordered eating, psychosocial impairment, and psychological distress at Time 1 predicted higher WBI at Time 2. Furthermore, higher WBI at Time 1 predicted higher body dissatisfaction, disordered eating, psychosocial impairment, and psychological distress at Time 2. Discussion: Weight bias internalization and psychosocial correlates were interrelated across time in Chinese adolescents. Improving WBI might be promising in the prevention of eating and body image disturbances and diminished psychosocial well‐being. Similarly, reducing eating and body image disturbances and improving psychosocial well‐being might be useful prevention targets in reducing WBI in Chinese adolescents. Public Significance: The present study represents an initial effort to explore bidirectional relationships between WBI and biopsychosocial health outcomes in Chinese adolescents. Findings suggest bidirectional relationships between WBI and psychosocial variables, highlighting the potential utility of incorporating WBI interventions into eating pathology and poor psychosocial well‐being prevention designs for Chinese adolescents.